Generation of Vestibular Tissue-Like Organoids From Human Pluripotent Stem Cells Using the Rotary Cell Culture System - Mattei, Cristiana; Lim, Rebecca; Drury, Hannah; Nasr, Babak; Li, Zihui; Tadros, Melissa A.; D'Abaco, Giovanna M.; Stok, Kathryn S.; Nayagam, Bryony A.; Dottori, Mirella (Frontiers in Cell and Developmental Biology, 2019)
Hair cells are specialised mechanosensitive cells responsible for mediating balance and hearing within the inner ear. In mammals, hair cells are limited in number and do not regenerate. Human pluripotent stem cells (hPSCs) provide a valuable source for deriving human hair cells to study their development and design therapies to treat and/or prevent their degeneration. In this study we used a dynamic 3D Rotary Cell Culture System (RCCS) for deriving inner ear organoids from hPSCs. We show RCCS-derived organoids recapitulate stages of inner ear development and give rise to an enriched population of hair cells displaying vestibular-like morphological and physiological phenotypes, which resemble developing human fetal inner ear hair cells as well as the presence of accessory otoconia-like structures. These results show that hPSC-derived organoids can generate complex inner ear structural features and be a resource to study inner ear development.